Critical discourse analysis in the Libyan President Al Ghaddafi’s last speech on 22\02\2011 during the Libyan uprising - Lutfi Mohammed, Alhemmair Alwash; Abdul Jabar, Mohd Azidan; Abdullah, Muhammad Alif Redzuan; Nimehchisalem, Vahid (Universiti Sains Islam Malaysia, 2021)
This study is expected to shed light on the further clarification of figurative language use and complement the research of social practices effects of discourse. It is expected to provide more information about the vocabulary and structural sets from the perspective of lexical and grammatical signals in the language of leaders. All that shall a coherent theoretical framework for CDA and metaphor. Most of Al Ghaddafi speeches were in vernacular language not in classical Arabic language because of his origins. Under the scope of CDA by applying the Fair clough 3D model. The objective of the study was to identify and analyze the over use of figurative language in Al Ghaddafi speech that produced opposite results, from gaining support to gaining failure of his rule, this shall be by categorizing the the mesin their social and cultural contexts, with a focus on the metaphor’s lexicon used in his last speech.CDA is an approach to language analysis that is concerned with issues of language, power and ideology. The figurative language is a useful tool in conveying messages to the audience when used in the specific purpose of speech in a balance but if used heavily it will give the opposite of what was hoped for, and this can be very clear evidence for all when we read what had happened and the results gained by Al Ghaddafi from his speech in the next few days after this horrible and terrifying speech.